2017
DOI: 10.15448/1984-7726.2017.1.25408
|View full text |Cite
|
Sign up to set email alerts
|

A identificação das variedades regionais do português brasileiro através da informação entoacional

Abstract: Este artigo está licenciado sob forma de uma licença Creative Commons Atribuição 4.0 Internacional, que permite uso irrestrito, distribuição e reprodução em qualquer meio, desde que a publicação original seja corretamente citada.Resumo: Este estudo tem como objetivo verificar se falantes do português brasileiro são capazes de reconhecer suas próprias variedades regionais a partir das informações entoacionais. Além disso, também pretende procurar pistas nas variações de F0 que possam justificar o desempenho dos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…8,9 Differences in verbal agility between the samples from different regions of Brazil may also be related to linguistic variations, especially in light of the previous observation that speakers from SP city have regional variations in speech that differ from other regions of the country. 23 In addition, it is important to bear in mind that most elderly in the FD were originally from other regions of the country, thus conferring more diverse speech characteristics. Moreover, results showed that average time living in the FD was 48 years for aged adults and 24 years for younger ones, factors which may further the systematization of speech characteristics of the population from the country's capital.…”
Section: Discussionmentioning
confidence: 99%
“…8,9 Differences in verbal agility between the samples from different regions of Brazil may also be related to linguistic variations, especially in light of the previous observation that speakers from SP city have regional variations in speech that differ from other regions of the country. 23 In addition, it is important to bear in mind that most elderly in the FD were originally from other regions of the country, thus conferring more diverse speech characteristics. Moreover, results showed that average time living in the FD was 48 years for aged adults and 24 years for younger ones, factors which may further the systematization of speech characteristics of the population from the country's capital.…”
Section: Discussionmentioning
confidence: 99%